THE EFFECT OF MEDIUM COMPOSITION ON Î²-GLUCOSIDASE PRODUCTION BY TRICHODERMA VIRIDE USING COW DUNG (FUDMA JOURNAL OF SCIENCES, 2020)
Different medium components were screened for their effect on Î²-glucosidase production.  Plackett-Burman experimental design was used and twelve experimental runs were generated using Design-Expert software to determine the main effect of glucose, sucrose, lactose, carboxymethyl cellulose, peptone, beef extract, NH4Cl, NaNO3, MnCl2 CaCl2 and K2HPO4  on Î²-glucosidase production. Out of the eleven medium components selected, six components (glucose, lactose, NaNO3, NH4Cl, MnCl2, K2HPO4) were found to contribute positively to the overall Î²-glucosidase production with a maximum production of 34.40Â±0.72 U/g. Thus, the use of Plackett-Burman experimental design in this study enabled the rapid identification of important medium components affecting the production of Î²-glucosidase.
Keywords: : Î²-glucosidase, Trichoderma viride, Plackett-Burman Design, Cowdung, Medium Components.